Formation of exceptional monomeric YPhos–PdCl2 complexes with high activities in coupling reactions. Issue 45 (10th November 2022) - Rodstein, Ilja; Kelling, Leif; Löffler, Julian; Scherpf, Thorsten; Sarbajna, Abir; Andrada, Diego M.; Gessner, Viktoria H.
Abstract : Ylide-substituted phosphines form monomer, air-stable PdCl2 complexes which feature a unique bonding situation between the metal and the phosphine and ylide donor and exhibit high efficiencies as precatalysts in C–C and C–X cross-coupling reactions. Abstract : The use of well-defined palladium(ii ) complexes as precatalysts for C–X cross-coupling reactions has improved the use of palladium catalysts in organic synthesis including large-scale processes. Whereas sophisticated Pd(ii ) precursors have been developed in the past years to facilitate catalyst activation as well as the handling of systems with more advanced monophosphine ligands, we herein report that simple PdCl2 complexes function as efficient precatalysts for ylide-substituted phosphines (YPhos). These complexes are readily synthesized from PdCl2 sources and form unprecedented monomeric PdCl2 complexes without the need for any additional coligand. Instead, these structures are stabilized through a unique bonding motif, in which the YPhos ligands bind to the metal through the adjacent phosphine and ylidic carbon site. DFT calculations showed that these bonds are both dative interactions with the stronger interaction originating from the electron-rich phosphine donor. This bonding mode leads to a remarkable stability even towards air and moisture. Nonetheless, the complexes readily form monoligated LPd(0) complexes and thus the active palladium(0) species in coupling reactions. Accordingly, the YPhos–PdCl2 complexes serve as highly efficient precatalysts for a series of C–C and C–X coupling reactions. Despite their simplicity they can compete with the efficiency of more complex and less stable precatalysts.